Layout design for efficiency improvement and cost reduction - G. Kovács (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2019)
In a reality of global competition, companies have to minimize production costs and increase productivity in order to boost com-petitiveness. Facility layout design is one of the most important and frequently used efficiency improvement methods for reducing operational costs in a significant manner. Facility layout design deals with optimum location of facilities (workstation, machine, etc.) on the shop floor and optimum material flow between these objects. In this article, the objectives and procedure of layout design along with the calculation method for layout optimization are all introduced. The study is practice-oriented because the described case study shows how the layout of an assembly plant can be modified to form an ideal re-layout. The research is novel and innovative because the facility layout design and 4 lean methods (takt-time design, line balance, cellular design and one-piece flow) are all combined in order to improve efficiency more significantly, reduce costs and improve more key performance indicators. From the case study it can be concluded that the layout redesign and lean methods resulted in significant reduction of the following seven indicators: amount of total workflow, material handling cost, total travel distance of goods, space used for assembly, number of workers, labor cost of workers and the number of Kanban stops.